2019
DOI: 10.1101/648246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Tn-Seq reveals common daptomycin resistance determinants inStaphylococcus aureusdespite strain-dependent differences in essentiality of shared cell envelope genes

Abstract: Antibiotic-resistant Staphylococcus aureus remains a leading cause of antibiotic resistance-associated mortality in the United States. Given the reality of multi-drug resistant infections, it is imperative that we establish and maintain a pipeline of new compounds to replace or supplement our current antibiotics. A first step towards this goal is to prioritize targets by identifying the genes most consistently required for survival across the S. aureus phylogeny. Here we report the first direct comparison of g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…We created a high-density transposon library, which comprises six sublibraries, in S. aureus USA300 by phage-based transposition as previously described 9 , 10 , 34 . The transposon library was treated with beta-lactams (8 μg mL −1 for mecillinam, 0.4 μg mL −1 for cefoxitin, and 0.1 μg mL −1 for oxacillin) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…We created a high-density transposon library, which comprises six sublibraries, in S. aureus USA300 by phage-based transposition as previously described 9 , 10 , 34 . The transposon library was treated with beta-lactams (8 μg mL −1 for mecillinam, 0.4 μg mL −1 for cefoxitin, and 0.1 μg mL −1 for oxacillin) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…4) and can contribute to developing a better understanding of how resistance emerges, as well as guide the development of new strategies to target resistant bacteria. Traditional TIS experiments performed by culturing transposon libraries with inhibitory but sublethal concentrations of antibiotics for several generations have been used to define a comprehensive non-essential gene complement involved in intrinsic resistance for many clinically important pathogens, including the notorious ESKAPE species (Enterococcus faecium, S. aureus, K. pneumoniae, Acinetobacter baumannii, P. aeruginosa and Enterobacter species) 18,[42][43][44] . These studies have shown that while antibiotics may have specific targets (for example, in cell wall synthesis, DNA replication or protein synthesis), the bacterial response to antibiotics is actually distributed across the genome.…”
Section: Overdispersionmentioning
confidence: 99%
“…We therefore focused our further analysis on the S. aureus salt stress response and conducted two additional TN‐seq screens to confirm the robustness of this approach (Figure a). TN‐seq screens were performed using a previously published library (Coe et al, ; Santiago et al, ) with six transposon variants and the library containing only one transposon variant used in the first TN‐seq experiment (Supporting Table for overview). The libraries were propagated for 17 generations in either LB or in medium containing 0.5 M NaCl (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…A previously published highly‐saturated S. aureus USA300 library with a mix of six different transposons was used (Coe et al, ; Santiago et al, ). In addition, a new transposon library with only the blunt transposon was produced using the same techniques as described (Santiago et al, ) containing approximately 1.2 million individual clones.…”
Section: Methodsmentioning
confidence: 99%